Nursing Clinical Preceptorship: Knowledge and Attitude of Nurse Educators Working in Teaching Institutes in India - Sheetal Barde1 , Sheela Upendra2 , Jasneet Kaur1 , Shital Waghmare1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Nursing is a field of clinical expertise, which deals with caring for the patients with illness andproviding them a quality nursing care. To provide a good quality Nursing care, it is very important that theNurses should be properly trained and expert in providing care. A clinical educator plays a very important intraining and updating nurses with the updated and current trends in Healthcare sector. Clinical preceptorshipis one of the best methods used to train the nurses in Clinical setting. Clinical preceptorship is a method ofteaching and guiding students by a knowledgeable nurse in medical area to train them in clinical Skills andtechniques.Clinical preceptorship is a concept which is mostly used in western countries. In India clinical preceptorshipis not practiced.Since it is a new concept in India scenario, this study evaluated the knowledge and attitude of NurseEducators towards clinical preceptorship.Methods: The study was conducted amongst Nursing Educators through online survey method.Results: More than 50 % of the Nursing professors does not have any knowledge about Nursing preceptorship.Out the educators having knowledge about Clinical preceptorship maximum had a positive attitude towardsit.Conclusion: The Nursing Educators in India are very much favourable with the concept of Clinicalpreceptorship, whilst there is knowledge gap present.